Perencanaan Portofolio Aplikasi Bisnis Pada PT. XYZ - Wawan Setiawan (Jurnal Informatika, 2023)
The development of digital applications in the current era requires companies to apply technology and information systems to make work easier and help compete with competitors to achieve a competitive advantage. PT. XYZ is a private company that focuses on warehousing and distributors of electronic goods located in the Tangerang City area. Based on the results of observations and interviews, there are problems such as stock management is still manual, employee payroll still uses excel, no sales promotion program, company profile website and CRM website. To map business applications at company XYZ, use Mc Farlan Strategic Grid analysis. The mapping in question is in the strategic, high potential, key operation, and support quadrants. analysis of internal and external conditions using SWOT analysis. Analysis of XYZ's internal environment includes elements of strengths and weaknesses. Meanwhile, the analysis of the company's external environment includes elements of opportunities (opportunities) and challenges (threats). Based on the results of the Mc Farlan Strategic Grid analysis, it was identified that there were two applications in the key operational application category, five applications as the support application category, three applications as the strategic application category, and one application in the high potential application category.